PENGETAHUAN PASANGAN USIA SUBUR TENTANG PEMILIHAN ALAT KONTRASEPSI DI KELURAHAN GUNUNG AYU WILAYAH KERJA PUSKESMAS TUNGKAL BENGKULU SELATAN: KNOWLEDGE OF COUPLES OF REPRODUCTIVE AGE ABOUT ELECTIONS CONTRACEPTIVE EQUIPMENT IN THE SUB-DISTRICT OF GUNUNG AYU, REGION SOUTH BENGKULU PRIVATE HEALTH CENTER WORK - Heni Angraini (Universitas Pahlawan, 2023)
The proportion of family planning needs has stagnated globally at around 77%, this study aims to determine the effectiveness of providing health education to couples of childbearing age about choosing contraceptives in Gunung Ayu Village, Manna City Public Health Center, South Bengkulu Regency. This study uses a quasi-experimental approach with a one group pre-post test design. The population of all EFAs who use contraception in Gunung Ayu Village in August 2022 is 147 people. Samples selection using purposive sampling. Data collection uses secondary and primary data. Data analysis was Wilcoxon Signed Ranks test. The results obtained is an effect of health education on the knowledge of couples of childbearing age about the selection of contraceptives, which means that the provision of effective health education on the knowledge of couples of childbearing age about the selection of contraceptives. It is hoped that the Puskesmas can increase the knowledge of couples of childbearing age by conducting regular health education.